HUBUNGAN KELINCAHAN DAN KECEPATAN DENGAN KETERAMPILAN MENGGIRING BOLA PADA TIM SEPAK BOLA USIA 14-15 DI SMPN 7 TAPUNG KABUPATEN KAMPAR - Triyantoro, Haris; Slamet, Slamet; Sulatio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine whether there is a relationship between agility and speed with dribbling skills in the Tapung N 7 Middle School Soccer Team in Kampar District. This form of research is a correlation study, the population in this study was the Tapung N 7 Junior High School soccer team in Kampar district. The sample in this study is the 7 Tapung Middle School Soccer Team totaling 18 people. From the calculation of the first analysis Relationships X1 and Y where the rtab at a significant level α (0.05) = 0.424 means r count (0.598)> rtab (0.424). Meaning hopotesis is accepted and there is a significant relationship between agility and dribbling skills on the football team Tapung N 7 Middle School Kampar District. The second analysis of the relationship between speed (X2) and dribbling skills (Y) where rtab at a significant level α (0.05) = 0.424 means r count (0.515)> rtab (0.424). Meaning hopotesis is accepted and there is a significant relationship between agility with dribbling skills on the Tapung 7 Junior High School Soccer team in Kampar district. The third analysis, namely the relationship of agility (X1) and Speed (X2) with dribbling skills (Y) is significant where where the rtab at the significant level α (0.05) = 0.424 means r count (0.620)> rtab (0.424). accepted and there is a meaningful relationship between agility and speed with dribbling skills on the Tapung 7 Junior High School Soccer team in Kampar district.Key Words: Agility, Speed and Dribbling Skills